Life skills activities for secondary students with special needs - Mannix, Darlene (San Francisco, CA : Jossey-Bass, 2021)
"Special Needs Education is curriculum and programming designed for students with disabilities. This education is designed to meet the needs of students with disabilities and maximize their skills and capabilities to lead independent and social lives. Specifically, there is a focus on life skills, or skills that are necessary to succeed in jobs and life after Special Needs Education. Life skills curriculum is typically a blend of academics, daily living, personal social skills, and occupational skills. Special Needs Education exists within the American public school system and can exist in the form of resource rooms, in special classes, or, in some cases, entire schools dedicated to supporting students with disabilities. Over 7 million students in the United States are in some form of special education, making the curriculum more important than ever"--
Keywords: Teenagers with disabilities -- United States -- Life skills guides; Life skills -- Study and teaching (Secondary) -- United States; Life skills -- United States -- Problems, exercises, etc